IPTEKS PENENTUAN KELAYAKAN KREDIT BANK PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK, KCP (KANTOR CABANG PEMBANTU) BAHU - Palilingan, Kartini A.T.; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2018)
The function of banking is to raise funds from the community and channel it to the public. In collecting funds in charge of the bank is a relationship fund and in channeling funds to the public the bank provides credit to help improve the economy and the welfare of the community. In the bank there is a credit relationship that is in charge of analyzing credit at this analytical bank that can see the feasibility and risk of bad credit.Keywords: Credit Analysis, Risk of bad credit